FROM MOON TO COMET LANDING: RE-IMAGINING (SCIENTIFIC) MEDIA EVENTS IN THE AGE OF TWITTER - Giglietto, Fabio; Rossi, Luca; Kim, Jiyoung (AoIR Selected Papers of Internet Research, 2015)
The Apollo 11 space mission took place 46 years ago. It was an international event covered by the largest media sources of the time. The global participation to this scientific and technological achievement is commonly considered a turning point in the history of media. In a near-perfect comparison to the famous 1969 event, on November 12 2014, the European Space Agency’s (ESA) Rosetta spacecraft and Philae made history landing for the first time on a comet. Launched toward Comet 67P/C-G in 2004, Rosetta traveled about 4 billion miles through the solar system before reaching the comet in August. The lander successfully made it to the surface of comet and Philae’s landing signal was received by Earth communication stations at 16:03 UTC On November 12. One minute later1, the Philae Lander Twitter account published the following update “Touchdown! My new address: 67P! #CometLanding”, putting an end to the dramatic waiting of users watching the live broadcast provided by ESA and NASA’s website. #CometLanding was therefore a (1) live transmission, (2) of a pre-planned event, (3) framed in time and space, (4) featuring a heroic personality or group, (5) having high dramatic significance. All but one “(6) the force of a social norm which makes viewing mandatory” of the necessary conditions identified by Katz as the basic ingredients of a media event, are clearly met (1980). While even traditional well established events such as the broadcast of the Olympic Games are increasingly facing challenges in fitting the original definition of the concept (Rivenburgh 2002), it is clear that a media event must, by definition, interrupt daily lives. Both broadcasters and the audience adjust their schedules to attend the event. Was this the case for #CometLanding? Can we still talk about media events when the audience feeling viewing as mandatory is a globally scattered elite, instead of the masses? How the traditional role played by the media changes when internet’s disintermediation make it possible for the creator of a media event to also act as narrator? In this proposal we present the preliminary results of an ongoing study on these issues. Results are based on the analysis of Twitter live commentary collected during the hours immediately before and after the landing of the rover on the comet.